Operational efficiencies across Asia Pacific airports - LAM, Shao Wei (Institutional Knowledge at Singapore Management University, 2009)
This paper analyses various dimensions of operational efficiencies in major Asia Pacific airports through Data Envelopment Analysis (DEA) models that simultaneously account for external macroeconomics and price factors. Results from this study show that technical, scale and mix efficiencies are high among the major Asia Pacific airports. In addition, significant disparities in cost efficiencies were detected amongst these airports. These disparities can be attributed to the presence of country-specific effect and differences in allocative efficiencies. A virtual airport is then introduced as a superior performer to rank the efficiency performances of airports.